Studies toward the Total Synthesis of Tianchimycins A and B: Construction of the Complete C1–C16 Framework - AnkiReddy, Sandeep; AnkiReddy, Praveen; Sabitha, Gowravaram (Synthesis, 2015)
A stereoselective synthesis of the complete C1–C16 framework of tianchimycins A and B is described. Key transformations include Horner–Wadsworth–Emmons, Evans aldol, Gilman’s and stereoselective alkylation reactions.
Keywords: Horner–Wadsworth–Emmons; Evans aldol; Gilman’s reaction; stereoselective alkylation; tianchimycins